Locus of Control and Self-Efficacy as Correlates of Secondary School Students’ Academic Achievement in Enugu State, Nigeria - Mamah, Miriam I.; Eze, Jude U.; Nwankwo, Evangeline U. (International Journal of Human Kinetics, Health and Education, 2022)
The growing rate of poor academic achievement of secondary school students and the contradictory results on the influence of locus of control and self-efficacy on academic achievement from previous studies warranted the study. The study assessed locus of control and self-efficacy as correlates of secondary school students’ academic achievement. Three research questions and two null hypotheses were formulated and posed respectively to guide the study. The hypothesis was tested at 0.05 level of significance. The study adopted a correlational survey research design. A sample of 500 SS3 students drawn by using multi-stage sampling procedures (simple random and proportionate stratified sampling technique) participated in the study. Locus of Control and Self-efficacy Questionnaire (LOCSEQ) and Students’ Academic Achievement Spreadsheet (SAAS) were used for data collection. The instruments were face-validated by three experts. Cronbach’s Alpha was used to determine the internal consistency of the questionnaire items and reliability coefficients of 0.81, 0.76 for clusters A and B respectively were obtained. Data collected were analyzed using regression analysis. The results showed that 35% and 32% of the variation in students’ academic achievement in physics is attributed to locus of control and self-efficacy respectively. Locus of control and self-efficacy significantly predicted students’ academic achievement. The study recommended, among others, that students must be made to understand that hard work and active participation during teaching and learning process is the key to academic success and that one’s ability determines one’s success in school.